Psychosocial Functioning for Preschool‐Aged Siblings of Children With Chronic Disorders: A Scoping Review. - Prentice, Caitlin M.; Fjermestad, Krister; Haukeland, Yngvild Bjartveit; Vatne, Torun M. (Child: Care, Health & Development, 2025)
Background: School‐aged siblings of children with chronic disorders, including somatic, neurodevelopmental and psychological diagnoses, are at a small but significant risk of experiencing psychosocial difficulties. It is unclear whether this is the case for such siblings when they are preschool age. Objective: This scoping review examined research describing psychosocial challenges and adaptation among preschool‐aged children who have a sibling with a chronic disorder, and interventions aimed to serve this population. Design: We searched online databases for peer‐reviewed studies published between 1998 and 2024 and identified 18 studies that reported psychosocial functioning such as psychological states, mental health variables and descriptions of experiences for 3‐ to 6‐year‐olds who were siblings of children with a neurodevelopmental disorder, somatic illness, mental illness or rare genetic disorder. Results: Of the 18 studies included, 15 were related to siblings of autistic children, and 12 of these aimed to study the development of autism in infants. Only two intervention studies were identified, and these had very small samples with maximum three participants in the 3‐ to 6‐year‐old age range. Conclusions: Results across the included studies suggest that preschool‐aged siblings may be at an increased risk of psychosocial difficulties, but it was difficult to draw definitive conclusions due to the large proportion of included studies related to the development of autism and the heterogeneity of study types represented. Future research should focus on the psychosocial functioning of preschool‐aged siblings and target preschool‐aged siblings of children with chronic disorders beyond autism.